2021
DOI: 10.1039/d0na01029d
|View full text |Cite
|
Sign up to set email alerts
|

Ambient processed (110) preferred MAPbI3 thin films for highly efficient perovskite solar cells

Abstract: Organic-inorganic hybrid perovskites have attracted intensive attention due to their exceptional optoelectronic properties. With a massive leap of efficiency from 3.8 % to 25.2 % in a decade, perovskite solar...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…S4 ). The positions of the peaks were measured and labelled with the corresponding Miller index 60 . The presence of multiple peaks, including (110), (114), (121), and (312) in the spectra of the samples 1, 2, 5 and 6 suggests the obtained films did not feature a preferred orientation.…”
Section: Resultsmentioning
confidence: 99%
“…S4 ). The positions of the peaks were measured and labelled with the corresponding Miller index 60 . The presence of multiple peaks, including (110), (114), (121), and (312) in the spectra of the samples 1, 2, 5 and 6 suggests the obtained films did not feature a preferred orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 15(b) shows the schematic illustration of the experimental setup to prepare the MA gas-mediated MAPbI 3 precursor solution. [275] For the first time, in 2015, Rao et al reported the compact SnO 2 nano colloid ETL for reproducible and high-efficiency MAPbI 3 PSCs. To obtain the smooth and uniform film, they did a TiCl4 treatment to the SnO2 layer.…”
Section: The Role Of Etl In the Performance Of Planar N-i-p Structure...mentioning
confidence: 99%
“…Reproduced with permission. [ 275 ] Copyright 2021, Royal Society of Chemistry. c) J‐V curves for the solar cell performance using the MAPbI 3 perovskite, the SnO 2 ETL prepared using ethanol and water as solvents.…”
Section: Common Solar Cell Structures and Their Effect On Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[ 8–12 ] Considering the simplicity and low‐cost required for large‐scale device manufacturing, it is highly desired to develop ambient air processed efficient and stable PSCs. [ 13–18 ] Though good device performance is achievable in air through humidity control, [ 19,20 ] it is still challenging to fabricate high performance PSCs in ambient air especially at high humidity level. Heat‐assisted film deposition methods are generally employed to prepare perovskite films in humid air, [ 21–23 ] however, the reported PCEs are much lower than that obtained in inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%